Cryopyrin‐Associated Periodic Syndrome. Issue 2 (14th August 2012) - Posch, Christian; Kaulfersch, Wilhelm; Rappersberger, Klemens
<x xml:space="preserve">Abstract</x> Abstract: Cryopyrin‐associated periodic syndromes (CAPS) are characterized by apparently unprovoked attacks of fever, rashes, and musculoskeletal and sensorineural inflammation accompanied by high acute‐phase reactants. Excessive interleukin‐1 (IL‐1) signaling appears to be a constant feature in the pathomechanism of the disease, driven by a gain‐of‐function mutation in the NLRP3 gene. Herein, we present the case of a 9‐month‐old boy with recurrent nonpruritic rashes and episodes of fever. The difficulties of early diagnosis due to initially mild clinical symptoms and the dramatic response to anti‐IL‐1 therapy after diagnosis emphasize the practical relevance of considering CAPS as a differential diagnosis in these patients.